Biochemical insight into soman intoxication and treatment with atropine, HI-6, trimedoxime, and K203 in a rat model - Pohanka, M; Pikula, J; Kuca, K; Kassa, J (Bratislavské lekárske listy, 2011)
OBJECTIVE: The present experiment is based on biochemical assessment of nerve agent soman intoxication and atropine, respectively atropine and HI-6, trimedoxime or K203 treatment in rats. BACKGROUND: Nerve agents are toxic substances irreversibly inhibiting enzyme acetylcholinesterase (AChE). Treatment is typically based on application of atropine and oxime reactivator. Atropine is able to protect overstimulation of muscarinic acetylcholine receptors. Application of oxime reactivator enable return of AChE activity and full suppression of intoxication. METHODS: In a total, fifteen biochemical markers were assayed in plasma or blood of intoxicated animals. 42 rats were divided into 7 groups each 6 individuals. The first group was exposed to atropine; the second group was exposed to one LD50 of soman and atropine. The groups 3-5 were exposed in a same way as the second group and were treated with oxime reactivators: HI-6 (group 3), trimedoxime (4) and K203 (5). The sixth group was control treated with saline solution only. The last (seventh) group was intoxicated with soman only. RESULTS: The most striking shifts were found for blood acetylcholinesterase and plasma creatinine, glucose, inorganic phosphate as well as uric acid. Lactate dehydrogenase and aspartate aminotransferase assays were useless due to soman interference. CONCLUSION: It was demonstrated that treatment was able to protect poisoned animals from metabolic disorder represented by hyperglycemia and nephropathy represented by hyperuricemia and elevated creatinine. Soman exposure and treatment with the oxime reactivators and/or atropine contains quite complex and still not well understood side mechanisms (Tab. 2, Fig. 1, Ref. 25).
Keywords: biologické markery; soman; zvířata; trimedoxim; atropin; Cholinesterase Reactivators; Oximes; Chemical Warfare Agents; oximy; Animals; Atropine; potkani Wistar; cholinesterasové inhibitory; antidota; Trimedoxime; Soman; Antidotes; Pyridinium Compounds; Biomarkers; Rats; Male; pyridinové sloučeniny; mužské pohlaví; krysa rodu Rattus; Rats, Wistar; chemické bojové látky; reaktivátory cholinesterasy; Cholinesterase Inhibitors